The fetish folk of West Africa - Milligan, Robert H. (Salt Lake City, UT : Project Gutenberg, 2023)
"The Fetish Folk of West Africa" by Robert H. Milligan is a scientific publication written in the early 20th century. The book explores the mental habits, beliefs, and cultural practices associated with fetishism among various West African tribes, aiming to reveal the richness of African humanity and folk-lore. It is complemented by illustrations and extensive anthropological insights, reflecting on the complexities of the African mindset, particularly in relation to the impact of colonialism and missionary efforts. The opening of the book introduces the reader to Milligan$1 (Bs perspective, detailing his motivation to document the culture and beliefs of the West African peoples contrasting them with Western views. He reflects on his experiences in Gaboon, addressing both the dangers$1 (Bsuch as disease and the toll of isolation on missionaries$1 (Band the uniqueness of the African worldview, particularly in terms of fetishism. He sets the stage for a deeper exploration of the intricate relationship between superstition, spirituality, and the social lives of the tribes, emphasizing that understanding these aspects is vital for appreciating the true essence of African identity. (This is an automatically generated summary.)s
Release date is 2023-12-22
Richard Tonsing, Peter Becker, and the Online Distributed Proofreading Team at https://www.pgdp.net (This file was produced from images generously made available by The Internet Archive)
Keywords: Fetishism -- Africa, West; Missions -- Gabon; Mpongwe (African people); Fang (African people)